Effects of fire on woody vegetation structure and composition across a distance gradient from the Kanda Vlei, Kazuma Pan National Park, Zimbabwe - Dube, Caleb; Chichinye, Angella; Mlambo, Donald; Mpofu, Ashley; Kundishora, Kudzai Ngqabutho (Journal of Forests, 2025)
Fire is a global phenomenon that influences vegetation structure and composition, shaping ecosystem dynamics in fire-prone landscapes. Despite its recognition as a key disturbance factor, little is known about its effects on woody vegetation across a distance gradient from the fire source, particularly in ecosystems characterized by vleis. To address this gap, we investigated the effects of fire on woody vegetation structure and composition across three distance gradients, replicated five times from the vlei. Fifteen rectangular plots (20x30m) were established along these gradients, with 15-20 trees selected per plot using a systematic design. A total of 509 woody plants were assessed. One-way ANOVA was used to test for significant differences in height, diameter, density, basal area, species diversity, and species richness using R software. Diversity indices, including the Shannon index for species diversity and the number of species for species richness, were calculated using the PAST4.03 software package to evaluate the composition of woody vegetation in the study area. The findings indicate a decrease in fire intensity and frequency with increasing distance from the vlei, resulting in varied fire regimes that simultaneously reduce species diversity and richness. Hayne dominates near the vlei, while fire-sensitive species such as Terminalia sericea, Combretum hereroense, Combretum apiculatum Sond., and Kirkia acuminata prevail further from the vlei. These results highlight the importance of considering spatial patterns in fire regimes and vegetation responses for effective prescribed burning, fire management planning, and conservation strategies. This study enhances understanding of fire-vegetation relationships and informs management strategies for fire-prone ecosystems.